Effects of phenethyl isothiocyanate on metabolism and on genotoxicity of dimethylnitrosamine and 2-amino-1-methyl-6-phenylimidazo[4, 5−b]pyridine (PhIP) - Knasmüller, Siegfried; Friesen, M. D.; Holme, J. A.; Alexander, J.; Sanyal, R.; Kassie, F.; Bartsch, Helmut (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 1996)
Phenethyl isothiocyanate (PEITC), a constituent of cruciferous vegetables, inhibited the genotoxic effects of N-nitrosodimethylamine (DMN) and of 2-amino-1-methyl-6-phenylimidazo[4,5−b]pyridine (PhIP) in differential DNA repair assays with E. coli K−12 strains in vitro and in animal mediated assays with mice. In Salmonella typhimurium, the mutagenic activities of DMN and PhIP measured after activation with S−9 homogenates from several organs of PEITC-treated mice were substantially lower than those obtained with homogenates of untreated animals as well. PEITC also reduced the formatio of micronuclei by DMN in metabolically competent Hep-G-2 cells of human origin but was ineffective in combination with PhIP. Biochemical investigations showed that the prevention of genotoxic effects of DMN by PEITC results from an inhibition of its α-hydroxylation. The effect of oral administration of PEITC on the formation of DNA adducts of PhIP was examined in the colon and liver of mice. No inhibition of adduct formation was observed in these experiments. Biochemical experiments showed that PEITC reduces not only the metabolic activation of PhIP via 2-hydroxyamino PhIP but also inhibits a detoxification pathway (formation of 4-hydroxy PhIP). The present results can be taken as an indication that the anticarcinogenic activities of isothiocyanates towards nitrosamines are paralleled by antimutagenic effects, and that probably no such protective effects occur in combination with heterocyclic amines. Furthermore, our findings show that the effects of chemopreventive agents demonstrated in bacteria in vitro cannot always be extrapolated to reactions occurring in intact mammalian cells.
Elektronische Reproduktion der Druck-Ausgabe 2. März 1999
Gesehen am 10.01.2024